The Role and Activation of Agricultural Risk Management Fund in Jordan (Case Study of Vegetable Farmers in Jordan) - Algharibeh, Ali Abdallah; Chemak, Fraj (Journal of Risk and Crisis Management, 2023)
The agricultural sector is considered very susceptible, thus requiring the implementation of developmental strategies to uphold its significance and facilitate its enhanced contribution to overall domestic production. This study aims to understand the role of the Agricultural Risk Management Fund and its activation methods from the perspective of vegetable farmers in Jordan. The study utilised a quantitative analytical approach, with a sample size of 186 individuals engaged in vegetable farming. The utilisation of descriptive analysis was employed To elucidate the role of the Agricultural Risk Management Fund and its activation methods. The research revealed that those who did not participate in the Risk Management Fund accounted for 64% of the sample. Among this group, the primary reason cited for non-participation was lack of interest, which was reported by the majority of respondents (38%), And The majority of participating farmers in the fund, accounting for 76%, believe that the subscription fee paid to the fund is not appropriate. To address this, farmers indicated that the suitable fee rate should be 17.3 Jordanian Dinars per donum. The study's findings suggest that it would be beneficial to conduct awareness workshops and lectures for farmers in order to familiarise them with the fund, its functions, objectives, and its significance within the agricultural industry. The study additionally highlights the importance of activating the Risk Management Fund in accordance with the desires of farmers, as well as the establishment of unambiguous regulations for risk mitigation and prevention. The focus of this study is on the Agricultural Risk Management Fund (ARMF) and its implications for vegetable growers in the Northern Jordan Valley region of Jordan. The primary concern is to examine the various risks faced by these farmers and how the ARMF can contribute to mitigating these risks.
Keywords: Agricultural Risk Management Fund; vegetable farmers; risk; Northern Jordan Valley; Jordan